Image and Identity in the Ancient near East Papers in Memoriam Pierre Amiet (Oxford)
vi, 191 sayfa
Keywords: “Image and Identity in the Ancient Near East: Papers in memoriam Pierre Amiet gathers the papers of two colloquia - one held in Pierre Amiet’s honour in Lyon in 2016 and the other held in Paris in 2017, as well as articles by colleagues who wished to dedicate a final tribute to him. The volume consists of two parts. The studies in the first part analyse the body as a biological entity as well as a social, sexual and cultural identity (persona). They show the emotional power of images, the means and media used to achieve this suggestive power, and the different audiences that are the privileged recipients of the different types of production. They also investigate the emotions as they are expressed through the gestures and attitudes of the characters represented. The second part includes articles that are more closely related to the themes that Pierre Amiet has tackled. Two articles deal with his favourite research theme, glyptics. One article takes up the problem of the formation of the state which Pierre Amiet had dealt with in several of his glyptic studies. Other papers are concerned with the organisation of craftsmen and statuary.” --